Population Ageing and Australia's Future - Kendig, Hal; McDonald, Peter; Piggott, John (ANU Press, 2016)
"This volume provides evidence from many of Australia's leading scholars from a range of social science disciplines to support policies that address challenges presented by Australia's ageing population. It builds on presentations made to the 2014 Symposium of the Academy of the Social Sciences in Australia. The material is in four parts: Perspectives on Ageing; Population Ageing: Global, regional and Australian perspectives; Improving Health and Wellbeing; Responses by Government and Families/Individuals. 'The Academy of the Social Sciences in Australia sees this volume as a major contribution to improving our understanding of Australia's population ageing. Social science research in this area truly underpins our ability as a nation to manage such demographic change, and its consequences for the economy and society. Such knowledge helps ensure that our citizens can live even better lives.' - Glenn Withers, President, ASSA"